PENGARUH PENGGUNAAN MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - nurvita sari samwar; Arwin Achmad; Rini Rita T Marpaung (Universitas Lampung, 2013)
Critical thinking skills in students XI Grade Science of Senior High School 7 Bandar Lampung not developed. This is because learning process dominated by teacher. One alternative that can be used to make students active in critical thinking is PBL models. The purpose of this study were to determine the effect of PBL models to the students' critical thinking skills. The design was a pretest-posttest non-equivalent. The samples in this study was students of XI Grade Science 2 and 3 where selected with clusster random sampling technique. The data of this study is in quantitative and qualitative data. Quantitative data obtained from the average value of the pretest, posttest, and N-gain statistically analyzed using t-test. Qualitative data taken from student learning activities observation sheet, and then analyzed descriptively.The results showed that the use of PBL models improve students' critical thinking skills with the average pretest score (24.11), posttest (68.95), and N-gain (59.86).Student learning activities that use the models PBL also increased from meeting I with an average of 55.09 to meeting II increased with an average of 69.91, and rise again on third meeting with the average of 80.32. Thus, application of the model PBL influential in improving critical thinking skills by students.Keywords: PBL Models, critical thinking skills, learning activities, and circulatory system.